Design and Development a Smart Control System for Temperature and Turbidity of Bio Floc Fish Ponds - Ambran Hartono; Ahmad Rofiq; Jalu Ahmad Prakosa; Ramli Ramli; Syafrijon Syafrijon (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2023)
Bio floc aquaculture techniques are present as a solution to increase the productivity of fish farming. However, until now there are still problems, namely regarding the quality of the water from the pond. In this study, a monitoring tool was designed using an ESP32 microcontroller with the support of a BME280 sensor, RTD PT100 to measure water temperature and a turbidity sensor to measure floc volume. Furthermore, this sensor is planted on Wi-Fi to be able to connect to the internet network for IoT applications so that it can be monitored in real time. Likewise, the display results from the monitoring of the application system are directly read on the Google sheet display and in real time. From the test results of the system built, obtained the accuracy level of the BME280 sensor is 96.5%, PT100 RTD is 94.6% and for the turbidity sensor is 98%. Meanwhile the observed air temperature value can reach 34.36°C, the water temperature reaches 28.75°C, and the floc ratio reaches 30.15 mL.L-1. From the results shown, it clearly indicates that the water quality monitoring system has been successful and is working very well.